2017
DOI: 10.1186/s13072-017-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Additional sex combs interacts with enhancer of zeste and trithorax and modulates levels of trimethylation on histone H3K4 and H3K27 during transcription of hsp70

Abstract: BackgroundMaintenance of cell fate determination requires the Polycomb group for repression; the trithorax group for gene activation; and the enhancer of trithorax and Polycomb (ETP) group for both repression and activation. Additional sex combs (Asx) is a genetically identified ETP for the Hox loci, but the molecular basis of its dual function is unclear.ResultsWe show that in vitro, Asx binds directly to the SET domains of the histone methyltransferases (HMT) enhancer of zeste [E(z)] (H3K27me3) and Trx (H3K4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
2
10
2
Order By: Relevance
“…While this is in agreement with several previously published studies, it contrasts with a number of reports suggesting that BAP1 and ASXL proteins participate in Polycomb-mediated silencing [24][25][26][27][28] . To formally investigate the interplay between BAP1 and Polycomb proteins, we analyzed the consequences of BAP1 loss in conjunction with loss of RING1B and EZH2, key members of PRC1 and PRC2, respectively ( Figure 4A).…”
Section: Bap1 Does Not Participate In Polycomb-mediated Silencingsupporting
confidence: 90%
See 2 more Smart Citations
“…While this is in agreement with several previously published studies, it contrasts with a number of reports suggesting that BAP1 and ASXL proteins participate in Polycomb-mediated silencing [24][25][26][27][28] . To formally investigate the interplay between BAP1 and Polycomb proteins, we analyzed the consequences of BAP1 loss in conjunction with loss of RING1B and EZH2, key members of PRC1 and PRC2, respectively ( Figure 4A).…”
Section: Bap1 Does Not Participate In Polycomb-mediated Silencingsupporting
confidence: 90%
“…Finally, since previous studies have reported a crucial role for the ASXLs in H3K27me3 deposition [24][25][26][27][28] , we further analyzed the genomic distribution of H3K27me3 in wild-type, BAP1, ASXL1, ASXL2, and EZH2 KO conditions. As shown in Figure 4E, there is a good genome-wide correlation in the localization of the mark between wild-type, BAP1, ASXL1 and ASXL2 KO cells, suggesting that loss of the ASXL proteins does not globally affect H3K27me3 distribution (see also Figure S4E for an example snapshot).…”
Section: Bap1 Does Not Participate In Polycomb-mediated Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that BAP1 and other PR-DUB subunits are frequently mutated in a variety of cancers with diverse origins (Wiesner et al 2011;Dey et al 2012;Carbone et al 2013;Murali et al 2013;Katoh 2013;Masoomian et al 2018;Zhang et al 2020), our findings also suggest that maintaining the cell type-specific balance between the activities that control H2AK119ub1 levels could play an important role in protecting cells from transformation. BAP1 has previously been proposed to regulate gene expression through diverse mechanisms, some of which are thought to function independently of H2AK119ub1 (Yu et al 2010;Dey et al 2012;Li et al 2017b;Wang et al 2018;Kuznetsov et al 2019;Campagne et al 2019). We now discover that BAP1 plays a surprisingly widespread role in supporting gene expression and show that this relies on BAP1 counteracting H2AK119ub1, as catalytic inactivation of PRC1 reverts the effects of BAP1 removal on gene expression.…”
Section: Discussionmentioning
confidence: 82%
“…Differential SET domain function also provides a possible functional explanation for the observation that the ETP Asx/ASXL1 is required for both trxG and PcG function [25, 26]. Asx has been found to interact with both the E(z) and Trx protein SET domains, controlling both activation and repression by modulating H3K4me3 and H3K27me3 levels at target loci [57]. However, the Asx family co-purifies in a complex containing the deubiquitinase BAP1 rather than EZH2 or MLL in both Drosophila and mammals [58], suggesting that further characterization of these interactions is required.…”
Section: The Set Domain and Methyltransferase Activitymentioning
confidence: 99%